In-terra-active 2.0 physical geology interactive CD-ROM. - Dunning, Jeremy; Brown, Phillip (Wadsworth Publishing Company, 1999)
Areas covered include: materials, surface, interior, and into the future. Each section contains an introduction, a critical thinking teaser, photographs, and animations.